Effects of periodontal therapy on eradication and recurrence of Helicobacter pylori infection after successful treatment. Issue 2 (February 2019) - Tongtawee, Taweesak; Wattanawongdon, Wareeporn; Simawaranon, Theeraya
Objectives: This study aimed to evaluate the effects of periodontal therapy on the efficacy of Helicobacter pylori eradication and on the recurrence of infection after eradication. Methods: We conducted a prospective randomized trial on 698 gastric H. pylori -infected patients, of whom 347 received gastric H. pylori treatment alone and 342 received gastric H. pylori treatment plus periodontal therapy. The presence of H. pylori and associated virulence genes were detected by real-time polymerase chain reaction. Results: After eradication of gastric H. pylori infection, the recurrence of gastric H. pylori was significantly lower in the gastric H. pylori treatment plus periodontal therapy group than in the group receiving gastric H. pylori treatment alone (OR 0.67; 95% CI 0.45 to 0.99), whereas the eradication rate was not significantly different (OR 0.87; 95% CI 0.68 to 0.98). There was a close relationship between the presence of H. pylori in saliva and its presence in the stomach. Conclusions: The oral cavity is an important reservoir for gastric H. pylori infection. Adjunctive periodontal therapy could enhance the efficiency of H. pylori treatment and reduce the recurrence of gastric H. pylori infection.